Our people - Multidimensional wellbeing in New Zealand - Keith McLeod (New Zealand Government, The Treasury, 2018)
This paper sets out to measure and reflect the wellbeing of New Zealanders across different areas of their lives, as expressed in the Treasury's Living Standards Framework (LSF). We are publishing the paper alongside the first version of the LSF Dashboard, which the Treasury is developing to inform its policy advice. The analysis in the paper provides the basis for the Our People section of the Dashboard. Reflecting the importance of the multidimensional nature of wellbeing, the paper presents estimates of wellbeing across multiple domains at the same time, assesses the extent to which these domains relate to each other, and looks at the distribution of wellbeing across these domains according to a set of key population demographic and socio-economic characteristics.
Keywords: 330